DIVERSITY OF BRITTLE STARS (OPHIUROIDEA) IN TALISE WATERS, NORTH SULAWESI - Doni Nurdiansah; . Supono (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2017)
Talise waters, located in North Sulawesi, is one of many coastal areas in Indonesia with sea grass cover extending along the reef flat. This ecological feature is beneficial for living habitat of associated fauna, including brittle stars. Brittle stars are group of Echinodermata reported to be abundantly found in sea grass ecosystem. However, the diversity of this fauna is less reported except as part of echinoderm studies. This research aims to investigate the diversity of brittle stars in Talise waters. Data were collected in July 2009 applying quadrant transect method. In total of 650 individuals belonging to 4 families (Ophiotrichidae, Ophiodermatidae, Ophiocomidae and Ophiuridae) and 10 species were recorded during this study. The diversity (H’=1.58), richness (D=1.69) and Evennes Index (J=0.89) was relatively higher compared to adjacent water in North Sulawesi such as Wori (H =1.64, D =1.38, J=0.85), Kema (H =1.3, D =0.38, J=0.36) but lower than East Likupang waters (H =1.95, D =2.42, J=0.97). Keywords: brittle star, diversity, richness, evennes, Talise waters